(untitled) (TAMADDUN NURI JURNALI, 2025)
In the process of studying fine arts terminology, it is undoubtedly necessary to examine the formation and development of the terminological system, as well as the linguistic properties of terms. This article analyzes art terms in the Karakalpak language by categorizing them into thematic groups. This approach significantly contributes to a clearer understanding of the meanings of fine art terms.